2004
DOI: 10.1002/hep.20359
|View full text |Cite
|
Sign up to set email alerts
|

Serum from patients with fulminant hepatic failure causes hepatocyte detachment and apoptosis by a β1-integrin pathway

Abstract: Hepatocyte transplantation is restricted by the impaired ability of hepatocytes to engraft and survive in the damaged liver. Understanding the mechanisms that control this process will permit the development of strategies to improve engraftment. We studied changes in liver matrix during acute injury and delineated the mechanisms that perturb the successful adhesion and engraftment of hepatocytes. Collagen IV expression was increased in sinusoidal endothelium and portal tracts of fulminant hepatic failure expla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 47 publications
1
18
0
Order By: Relevance
“…There was considerable variation in the extent of apoptosis induced by different LFP samples, not surprisingly reflecting the variability in the clinical status of the patients, and indeed some samples showed a similar level of apoptosis to normal plasma. This report enhances the observation of Newsome et al (5) who used a single pool of serum from a panel of liver failure patients to show enhanced in vitro apoptosis on primary human hepatocytes after loss of adhesion. There are important differences between the techniques used, however.…”
Section: Mars Dialysis and Apoptotic Effects Of Liver Failure Plasma 739supporting
confidence: 85%
See 1 more Smart Citation
“…There was considerable variation in the extent of apoptosis induced by different LFP samples, not surprisingly reflecting the variability in the clinical status of the patients, and indeed some samples showed a similar level of apoptosis to normal plasma. This report enhances the observation of Newsome et al (5) who used a single pool of serum from a panel of liver failure patients to show enhanced in vitro apoptosis on primary human hepatocytes after loss of adhesion. There are important differences between the techniques used, however.…”
Section: Mars Dialysis and Apoptotic Effects Of Liver Failure Plasma 739supporting
confidence: 85%
“…These toxic factors affect many systems (e.g., systemic vasculature and brain) and may have deleterious effects on liver cells themselves, by inhibiting regeneration and via induction of cytotoxicity (4)(5)(6)(7)(8). Potentially, this initiates a downhill cycle with further reduction in liver-specific function, persisting long after withdrawal of the insult that precipitated liver failure.…”
mentioning
confidence: 97%
“…Further, several previous studies had shown that, in vitro, integrins are involved in resistance to cytotoxins. [36][37][38][39][40][41][42] Again, we used the chemotherapeutic compounds cisplatin, daunorubicin, doxorubicin and romidepsin, but now together with a 25 amino-acid long polypeptide, derived from netrin-1, which had been shown to interact with α6β4 integrin and block adhesion-mediated signaling. 43 We reasoned that if the netrin-1 derived peptide reduced cell adhesion, it should diminish drug resistance.…”
Section: Resultsmentioning
confidence: 99%
“…Once the bacteria initiate the process of internalization, contact between the extracellular matrix (ECM) and integrin are broken, allowing endocytotic factors to concentrate receptors at the site of bacterial binding [34]. Loss of adherence of integrin to ECM then induces apoptosis [35,36].…”
Section: Discussionmentioning
confidence: 99%